Karakteristik Model Batere Sekunder Menggunakan Elektroda PANI-NMP - S. Hidayat; M. O. Tjia (Institut Teknologi Bandung, 2002)
Polyaniline that was plasticized with n-methyl pirrolidinone (PANI-NMP) was investigated as secondary battery electrode. The study was conducted on two model batteries having a configuration of [stainless steel⏐ PANI-NMP⏐ LiClO4 + PEO + acetonitril ⏐ Li-Al] and [stainless steel⏐ PANI-NMP⏐ LiClO4 + PEO +⏐Li-Al] respectively. The working voltage of each battery system were found to vary respectively from 1,65 volt to 3 volt and from 1,5 volt to 3 volt. The Coulombic efficiency of the first model is 78,3% related to the optional charge capacity of 10,4 Ah/kg, while that of the second model only attains a value of 60% related to the optional charge capacity of 5,2 Ah/kg. Coulombic efficiency of the battery decreases respectively from 80,6% to 47,8% and from 72,2% to 65,6 after 20 cycles of recharging.